Case report: Spontaneous bilateral intraocular lens dislocation in a patient with homocystinuria - Yao, Bangtao; Chen, Xujian; Liu, Gang; Zhao, Xiaogui (Frontiers in Cardiovascular Medicine, 2022)
Abstract Background: Spontaneous bilateral intraocular lens dislocation of the vitreous cavity is a rare ocular disorder. This article aims to comprehensively describe bilateral spontaneous intraocular lens dislocation with unilateral lamellar macular hole and retinoschisis in a Chinese woman with homocystinuria. Case presentation: A 72-year-old Chinese woman with homocystinuria presented with painless bilateral blurring of vision. The slit lamp showed the absence of lenses in both eyes. B-ultrasound and orbital computed tomography (CT) demonstrated bilateral posterior dislocation of the crystalline lenses, and spectral-domain optical coherence tomography (SD-OCT) revealed a lamellar macular hole and retinoschisis in the right eye. Biochemical examination demonstrated that the total homocysteine level was moderately elevated. Conclusions: This report is the first to present an extensive and valuable description of bilateral intraocular lens dislocation with unilateral lamellar macular hole and retinoschisis secondary to homocystinuria. We have demonstrated that this case was spontaneous and chronic. CT is an effective diagnostic tool for patients with ectopia lentis. Early diagnosis and suitable management of patients with homocystinuria are essential to prevent these complications.